DEVELOPMENT OF E-MODULES CONTAINING RELIGIOUS VALUES IN CLASS XI SMA/MA CELL MATERIAL - Afriansyah, Dini; Sabila, Nanda (Bioedunis Journal, 2024)
The purpose of learning science is the formation of students' attitudes of belief, feeling the nature of creation and the majesty of God Almighty, for that requires innovative learning media, namely E-Modules with religious / Islamic values. This study aims to produce e-modules with religious values on Cell material in class XI SMA/MA that are valid and practical. The development model is Research and Development type ADDIE which consists of 5 stages namely Analysis, Design, Development, Implementation, and Evaluation, but limited to Development only. The evaluation stage is validity and practicality using one-to-one evaluation and small group. Samples using purposive sampling technique with criteria, namely students with high, medium, and low academic abilities. Data collection through observation, interviews, and questionnaires. given to 5 experts/validators with various expertise namely media, material, Qur'anic interpretation, and Language and Values. Practicality questionnaires were given to one biology teacher, 3 students (one-to-one evaluation), 10 students (small group trial). The results showed that e-modules with religious value content were feasible, the assessment category was very valid and practical based on media experts 99%, material experts 90%, Al-Qur'an interpretation experts 93%, language experts 99%, religious value experts 98% and the practicality trial obtained an educator score of 97%, one-to-one evaluation 91%, small group trial 89%.Keywords: ADDIE, E-Module, Religious Value, Cell, Biology Education, Islam.